Efforts to Improve Scientific Literacy of Students through Guided Inquiry Learning Based on Local Wisdom of Baduy’s Society - Saefullah, Asep; Samanhudi, Udi; Nulhakim, Lukman; Berlian, Liska; Rakhmawan, Aditya; Rohimah, Bai; El Islami, R. Ahmad Zaky (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
AbstractThe aim of this study was to determine the influence of guided inquiry learning model toward the improvement of students’s scientific literacy in integrated science learning on environmental conservation concept based on local wisdom of Baduy’s society. This study used Research and Development method through pretest and posttest test before and after the guided inquiry learning was done. The objects of this study were 31 students who were following the integrated science lecture in 5th semester which is prospective science teacher. The results showed that there was an improvement in students' scientific literacy after guided inquiry learning (was applied) as shown with a gain value of 0.16 (N-Gain = 0.16) which was included in the medium category. Based on this result, it can be concluded that there is the influence of guided inquiry learning model toward the improvement of students’s scientific literacy in integrated science learning on environmental conservation concept based on local wisdom of Baduy’s society. Keywords: Scientific Literacy, Guided Inquiry, Local Wisdom, Baduy’s Society